The Role of Emotional Intelligence in 21st Century Classrooms - Iqbal, Khurshed; Fauziyati, Wiwin Rif’atul; Purnama, Medina Nur Asyifah; Abdullah, Saman Ahmed; Tesema, Ayenew Kassie (CV. Edujavare, 2024)
Integrating Emotional Intelligence (EI) into educational practices has gained significant attention due to its potential to enhance student outcomes in the 21st-century classroom. This study aims to explore the role of EI in classroom dynamics, focusing on its impact on classroom management, student-teacher relationships, and overall academic and emotional development. Using a qualitative research approach, the study employed case studies and in-depth interviews with teachers and students across multiple schools. Data were analyzed using thematic analysis to identify patterns and themes related to EI's application in the classroom. The findings revealed that teachers who effectively applied EI strategies created more supportive, inclusive environments, improving student engagement, academic performance, and stronger emotional regulation. Students in these classrooms also demonstrated improved social-emotional skills, such as empathy and conflict resolution, contributing to more positive peer interactions. However, challenges such as a lack of training and resources were identified, which hindered the consistent implementation of EI practices. The study concludes that EI is critical in fostering positive learning environments and should be integrated into teacher training and curricula. The research contributes to the growing body of knowledge on EI in education and advocates for systemic changes to ensure its effective application across schools.